2018
DOI: 10.1007/s12010-018-2815-2
|View full text |Cite
|
Sign up to set email alerts
|

Production of Recombinant N Protein of Infectious Bronchitis Virus Using the Baculovirus Expression System and Its Assessment as a Diagnostic Antigen

Abstract: The avian coronavirus-infectious bronchitis virus (AvCoV-IBV) is recognized as an important avian pathogen, and new viral variants are a continuous threat to the poultry industry worldwide. Sensitive diagnostics and efficacious vaccines are necessary to combat IBV infections in chickens. The aim of this study was to produce recombinant N protein of IBV in the baculovirus system to use in ELISA diagnostic tests in order to enable the assessment of the sero-prevalence and risk of IBV infections in chickens in Tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…In house, ELISA methods were standardized to analyze the sera of cats for the presence of antibodies to SARS-CoV-2 by using the purified recombinant S and RBD proteins of SARS-CoV-2 as the target antigen. Indirect ELISA protocols were standardized using checkerboard titration protocol, as described previously (30). For this, two-fold dilutions of the S and RBD proteins were prepared at a range of 250-4,000 ng/ml in PBS (Sigma) on 96-well ELISA plates (MaxiSorb flat bottom).…”
Section: Standardization Of Elisa For Estimation Of S and Rbd Antibody Levels In Serum Samples Collected From Catsmentioning
confidence: 99%
“…In house, ELISA methods were standardized to analyze the sera of cats for the presence of antibodies to SARS-CoV-2 by using the purified recombinant S and RBD proteins of SARS-CoV-2 as the target antigen. Indirect ELISA protocols were standardized using checkerboard titration protocol, as described previously (30). For this, two-fold dilutions of the S and RBD proteins were prepared at a range of 250-4,000 ng/ml in PBS (Sigma) on 96-well ELISA plates (MaxiSorb flat bottom).…”
Section: Standardization Of Elisa For Estimation Of S and Rbd Antibody Levels In Serum Samples Collected From Catsmentioning
confidence: 99%
“…The in-house indirect ELISA (iELISA) protocols using S, S1 and RBD proteins were validated as described previously [ 16 , 17 ]. The validation studies were performed as follows: Initially, a total of 292 sera from 222 SARS-CoV-2-vaccinated and 70 SARS-CoV-2-infected humans (clinically ill and confirmed SARS-CoV-2-RNA positive by RT-PCR) were tested using a commercial ELISA (SARS-CoV-2 IgG II Quant, Abbott Diagnostics, IL, USA) for the presence of SARS-CoV-2 IgG antibodies.…”
Section: Methodsmentioning
confidence: 99%
“…Infectious bronchitis (IB) is caused by the avian coronavirus-infectious bronchitis virus (AvCoV-IBV), which is recognized as a severe threat to the poultry industry globally owing to that it affects chickens of all ages and causes respiratory and nephrotic syndromes in broilers, as well as impairs egg production in layers and breeders [ 1 , 2 , 3 ]. AvCoV-IBV that belongs to the genus Gamma-coronavirus within the family of Coronaviridae in the order Nidovirales, is an enveloped, positive single-stranded RNA virus [ 4 ]. The 27 to 28 kb genome of AvCoV-IBV encodes several structural proteins, including spikes (S), membranes (M), envelopes (E), and nucleocapsids (N) protein [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, whole IBV particles is tedious for producing procedures including virus proliferation and purification to cause the high price of the commercial ELISA kits, which limits its application [ 9 ]. Many studies indicated that recombinant S and N proteins from prokaryotic, yeast, or baculovirus systems could provide a rapid and large-scale detection method for IBV antibody infection [ 4 ]. The S protein of IBV has highly mutation in different IBV strains, which restricted its application in for detecting the IBV antibody.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation